MATERIALS OF THE AMUDARYA EXPEDITION IN THE SCIENTIFIC LITERATURE ON THE HISTORY OF THE PEOPLES OF THE SOUTHERN ARAL SEA REGION (Based on scientific literature published during the independence period of the Republic of Uzbekistan) - Taspolatova, Guljahan Edenbaevna (SCIENCE and SOCIETY, 2026)
This article examines scientific works produced during the period of independence of the Republic of Uzbekistan that utilize materials from the Amu Darya Scientific Expedition. The results of the expedition sent by the Tsarist Russian government to the region are valuable as they help us obtain accurate information about the history of the Karakalpaks 150 years ago, their living conditions, and the occupations of both them and neighboring peoples in the area. Therefore, a detailed and in-depth study of the Amu Darya expedition materials in the future is considered one of the pressing issues in researching the history of Karakalpakstan.